Evaluation of view to women's health and gender in television channels' daytime programmes - Nilay Etiler; Ülkü Zengin (Turkish Society of Public Health Specialists, 2015)
Objective: Daytime programmes in television channels generally target women by considering several topics including health which are points of interests for women. In this study, we studied the contents of the daytime programmes of TV channels to women's health and gender problems and to determine the transmitted knowledge. Methods: This descriptive study applied qualitative assessment to daytime programmes in TV channels showing during May-June 2013. 11 channels which have daytime programmes about women and health, A total of 22 sessions were included in the study where 18 were health and 4 were general women programmes in 11 channels which have daytime programmes. Results: The most discussed issues are about slimming and healthy nutrition and beauty issues in those programmes. Women's reproductive health issues (labour, menopause etc.) or their musculoskeletal disorders were rarely discussed. In the discussions, gender roles of women are presented with many hidden messages. In addition, we found that women were treated as consumers with advertising of many items from health care to several materials including shoes sole and cooker pots. Conclusion: These kinds of programmes are functioning to reproduce existing gender roles in Turkey where the gender gap is already deep. The health topics discussed do not overlap with women's health problems our society's health problems were densely presented with beauty and esthetic contents. However these programmes could be used both as a tool in women's health promotion and as an intervention to decrease the gender gap in our society, a gap that is increasing gradually. There is a necessity that relevant institutions of the government should plan and control these issues.